Bảo vệ chống ăn mòn hợp kim đồng bằng lớp phủ hữu cơ chứa polypyrol - Hiền, Nguyễn Thị Lê (Vietnam Journal of Chemistry, 2012)
A fine, stable and compact passive film is natural formed on brass surface in the 3% NaCl solution. This film with a resistance of 700 W.cm2 can prevent the brass from corrosion. Corrosion current calculated from Tafel equation is about 7e-7 A.cm-2. Results obtained by electrochemical impedance measurement show that the use of the primary coating of epoxy E828 or X75 containing polypyrrole improves significantly the protection efficiency against corrosion of brass. After more than one month of immersion in 3% NaCl, these coating show pure capacity comportment. The presence of polypyrrole in the coating increases adherence and decreases the water take-up of the coating, meaning that the coating is more stable and its capacity is quasi unvaried with time.